2022
DOI: 10.3389/fsufs.2022.913211
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interaction on Tropical Maize Hybrids Under Normal Irrigation and Waterlogging Conditions

Abstract: Unpredictable rainfall in the tropics often increases the risk of waterlogging or even flooding in agricultural lands, hindering the efforts to fulfill maize demands. Breeding maize for waterlogging tolerance is necessary yet challenging since performing varietal testing on a set of hybrids might be biased toward the presence of genotype and environment interaction (GEI). This study aimed to elucidate the GEI effects on yield and related agronomic traits of tropical maize hybrids under normal irrigation and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
2
11
1
Order By: Relevance
“…The significance of the genotype-by-environment interaction shows that the genotypes' agronomic traits vary from one location to another, while the non-significance of genotype-by-environment interaction for some traits showed that the traits did not diverge from one location to another. In the corn hybrid study for grain yield, Haruna et al (2017); Azrai et al (2022), andHudson et al (2022) reported findings in multi-environment trials where the main proportion of total phenotypic variation was ascribed to the environment and comparatively minor sources of variation to genotype, while in this present study, a larger proportion of variation was attributed to the genotypes. This study revealed very highly significant differences in genotypes and significant differences in environments, which could be credited to environmental conditions, the genetic diversity of the genotypes, and the effects of the interaction between the genotypes and environments.…”
Section: Combined Analysis Of Variance For Agronomic Traitscontrasting
confidence: 43%
See 3 more Smart Citations
“…The significance of the genotype-by-environment interaction shows that the genotypes' agronomic traits vary from one location to another, while the non-significance of genotype-by-environment interaction for some traits showed that the traits did not diverge from one location to another. In the corn hybrid study for grain yield, Haruna et al (2017); Azrai et al (2022), andHudson et al (2022) reported findings in multi-environment trials where the main proportion of total phenotypic variation was ascribed to the environment and comparatively minor sources of variation to genotype, while in this present study, a larger proportion of variation was attributed to the genotypes. This study revealed very highly significant differences in genotypes and significant differences in environments, which could be credited to environmental conditions, the genetic diversity of the genotypes, and the effects of the interaction between the genotypes and environments.…”
Section: Combined Analysis Of Variance For Agronomic Traitscontrasting
confidence: 43%
“…The two concepts focus on environments in terms of their ability to detect the best genotypes (discriminativeness) and to adequately represent the test environments (representativeness) (Yan and Tinker, 2006;Oladosu et al, 2017;Khan et al, 2021). The use of multi-environmental trials is very beneficial because it helps to avoid overestimation of heritability and genetic variance, which are always observed with one location experiment (Azrai et al, 2022). Our study revealed the environments closely related, demonstrating the discriminativeness ability and the representativeness of the test environments.…”
Section: Discriminativeness Vs Representativeness Analysismentioning
confidence: 54%
See 2 more Smart Citations
“…Interpretation of the genotype x environment interaction is essential to increase productivity with the positioning of the cultivar in the microregion and its predictability of performance according to the sowing date [1]. Traditionally, analysis methods of the genotype x environment interaction have been used for the positioning of cultivars, however, the interpretations obtained after obtaining data and generalizations about the environment do not allow the application or extrapolation of results for all regions [2][3]. However, when the environments are well characterized, conclusions on cultivar performance are extrapolatable, as used nitrogen levels in rice [4] or used water deficit environments in maize [5].…”
Section: Introductionmentioning
confidence: 99%